Determinants of inter-regional migration in the Baltic countries - Mihails Hazans (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
We show that Estonia, Latvia and Lithuania despite small geographical size feature considerable and persistent regional disparities. Registered migration rates have declined dramatically since the last years of Soviet era, yet they are high by international standards. Evidence from regional inflows and outflows in Latvia and from Estonian labour force survey is used to show that regional unemployment and especially wage differentials, as well as demographic factors, have a significant impact both on gross and net migration flows. Age and education effects are consistent with predictions of the human capital model of migration. Unemployed persons, as well as commuters between regions, are significantly more likely to become migrants in Estonia.
Keywords: J61; J31; J15; P31; P52; 330; Migration; Regional Disparities; Regional Labour Markets